Literasi Digital: Perilaku dan Interaksi Sosial Masyarakat Bengkulu Terhadap Penanaman Nilai-nilai Kebhinekaan Melalui Diseminasi Media Sosial - Prio Utomo; Fiki Prayogi (Indonesian Journal of Social Science Education (IJSSE), 2021)
The purpose of this study is to find out (1) people's social behaviors and interactions through social media dissemination; (2) the behavior and social interaction of the community towards the cultivation of diversity values; and (3) imlpementasi planting of diversity values of the people of Bengkulu. This type of research uses quantitative research approach with survey research method. The research was conducted in Bengkulu Province in 2020. The population of this study is the people of Bengkulu City, Mukomuko District, Kepahiang and Seluma District. Research sample as many as 400 respondents, sampling using multistage random sampling. Data collection using questionnaires via mobile and deep interview. Data analysis using survey application (alvara-analytic). The findings showed (1) the people of Bengkulu are literate towards digital literacy and actively use social media; (2) the values of diversity instilled by society include the values of tolerance and harmony, justice and equality, mutual cooperation and help, solidarity and togetherness, and democratic values; (3) the index of diversity values of Bengkulu people in the good category (82.1%), the dimension of understanding of community diversity by 94.1% and the dimension of community diversity attitude by 70.1%.